Wady wrodzoneUnusual presentation of the right atrial thrombus formation in a child with acute lymphoblastic leukaemia: a case report - Karolczak, Maciej A.; Mądry, Wojciech; Wyhowski, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Right atrial or vena cava thrombi are well-known complications of indwelt central venous catheters. A right atrial thrombus unrelated to the tip or body of a catheter is an unusual finding. We present a case of an isolated, calcified, coral-like mural thrombus attached to the right atrial appendage in a paediatric patient with acute lymphoblastic leukaemia. Diagnostics and treatment are discussed in detail.